ผลของการแทนที่แป้งข้าวเจ้าด้วยแป้งข้าวเหนียว แป้งมันฝรั่ง แป้งมันสำปะหลัง และแป้งเท้ายายม่อมต่อลักษณะคุณภาพของก๋วยเตี๋ยวสดและก๋วยเตี๋ยวอบแห้ง - พรทิพย์ อ่อนนิ่มนิตย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This research aimed to study the effect of type and substitution level of selected flours on quality characteristics of fresh rice noodle. Quality changes of the noodles during ambient and refrigerated storage, as well as cooking quality of the dried noodles were also investigated. Rice flour in the noodle recipe was substituted by glutinous rice, potato, cassava or arrowroot flour at the ratio of 90:10, 80:20, 70:30 and 60:40 by weight. By monitoring the pasting behavior, the highest pasting temperature and setback, with the lowest peak viscosity, were shown by rice flour. Peak viscosity was highest in potato flour while setback was lowest in glutinous rice flour. Pasting behavior of the mixed flour samples was found to correlate with that of the substituting flour. In the matter of gelatinization, rice, potato, cassava and arrowroot flours possessed higher gelatinization temperature than glutinous rice flour. Color characteristics of the fresh rice noodle were virtually unaffected by the substitution of rice flour with glutinous rice, potato or cassava flour. However, addition of arrowroot flour resulted in an increase in +b*, hue angle and chroma, with a concomitant decrease in whiteness index. In terms of textural properties, flour substitution caused a decrease in firmness and hardness, with no apparent effect on springiness. Glutinous rice flour substitution brought about a significant increase in adhesiveness with a decrease in cohesiveness (p≤0.05). For the storage study, noodle samples with substitution ratio of 90:10 and 70:30 were kept at room temperature (25 °C) for 1 day or at refrigerated temperature (4 °C) for 5 days. With increasing storage time, an increase in amylopectin recrystallization was detected in all samples. The highest amylopectin recrystallization was demonstrated in the rice flour sample while similar levels of amylopectin recrystallization were observed in all other samples. With increasing storage time, there were a decrease in water soluble starch content and an increase in firmness in all samples. Compared to those stored at room temperature, more pronounced changes in amylopectin recrystallization, water soluble starch content and firmness were noticed in the refrigerated samples. Regarding dried rice noodle quality, glutinous rice flour substitution resulted in an increase in cooking loss. Meanwhile, rehydration ratio was similar in all samples. Substituting rice flour by other flours caused a decrease in firmness and hardness of the rehydrated noodle. The glutinous rice flour-containing samples exhibited a significant difference in terms of firmness, hardness, adhesiveness, springiness and cohesiveness, compared to the rest of the samples.